2018
DOI: 10.1007/s00705-018-3754-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic analysis of Aleutian mink disease virus isolates in north-east China

Abstract: Aleutian mink disease is the most important disease in the mink-farming industry worldwide. So far, few large-scale molecular epidemiological studies of AMDV, based on the NS1 and VP2 genes, have been conducted in China. Here, eight new Chinese isolates of AMDV from three provinces in north-east China were analyzed to clarify the molecular epidemiology of AMDV. The seroprevalence of AMDV in north-east China was 41.8% according to counterimmuno-electrophoresis. Genetic variation analysis of the eight isolates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Morever, 23 Chinese samples had similar changes in some fixed positions, especially in the hypervariable regions. These results indicated that Chinese AMDV strains had a high degree of similarity among themselves, while they showed the difference from ADMV strains in other countries, which is consistent with the previous studies [ 9 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Morever, 23 Chinese samples had similar changes in some fixed positions, especially in the hypervariable regions. These results indicated that Chinese AMDV strains had a high degree of similarity among themselves, while they showed the difference from ADMV strains in other countries, which is consistent with the previous studies [ 9 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Currently, there is no available vaccine, and the knowledge about AMDV diversity and molecular epidemiology will help to prevent AMD from spreading. Previous studies reported that a large number of mink farms were affected by AMDV in China, based on VP2 or NS1 gene from samples of mink tissues, such as spleen, and plasma, especially during the pelting season [9,10]. However, this epidemiological survey of AMDV is commonly limited by sampling time and quantity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morever, 23 Chinese samples had similar changes in some fixed positions, especially in the hypervariable regions. These results indicated that Chinese AMDV strains had a high degree of similarity among themselves, while they showed the difference from ADMV strains in other countries, which is consistent with the previous studies [9,15].…”
Section: Discussionsupporting
confidence: 91%